Primary non-Hodgkin lymphoma of the stomach: endoscopic pattern and prognosis in low versus high grade malignancy in relation to the MALT concept. Issue 4 (October 1996) - Taal, B G; Boot, H; van Heerde, P; de Jong, D; Hart, A A; Burgers, J M
Abstract : BACKGROUND: Various histological classifications developed for nodal lymphomas failed to be of value in extranodal lymphomas. More recently, gastric lymphoma is considered to represent a distinctive group derived from mucosa associated lymphoid tissue (MALT). AIM: To study the prognostic value of malignancy grading based on the concept that most gastric lymphomas are of MALT origin, the endoscopic as well as clinical characteristics in 114 patients with primary gastric non-Hodgkin's lymphoma were evaluated. RESULTS: In univariate analysis, patients with low grade lymphoma (n = 51) were younger, had less advanced stage, and less frequently bulky disease than those with high grade lymphoma (n = 63). In multivariate analysis weight loss and increased erythrocyte sedimentation rate were significantly less frequent in low grade (45% and 22%) compared with high grade lymphoma (75% and 53%). In low grade lymphoma endoscopic findings were often interpreted as a benign condition (27 of 51), in contrast with high grade lymphoma, where carcinoma was most frequently (37 of 63) suspected. In low grade lymphoma complete remission rate was 92%, and five year survival 75%, In high grade lymphoma results were significantly less favourable (p = 0.0001): complete remission in 68%, and a five year survival of 46%. CONCLUSION: Malignancy grading was strongly correlated with treatment outcome; endoscopically low grade lymphoma was often hard to distinguish from benign conditions, whereas high grade lymphoma often revealed carcinoma-like features.